A Review on Basic Principles of an E-Assessment System (International Journal of Engineering and Computer Science, 2014)
Assessment is the basic fundamental activity of all learning environments. Therefore all learning management systems (LMS) provide the assessment facilities like (e.g., the formation, implementation, and   valuation of multiple choice tests as well as programming assignments).This  paper mainly  elaborates the   principles of service oriented paradigms, those are applicable for routine evaluation of  programming assignments as well as multiple choice questions.   The   most prominent aspect of this   assessment solution is, it can assess the programs written in any programming languages. Moreover, it can   be easily interfaced with different existing learning management systems. This paper also   presents the  design of  a  flexible  e-Assessment system based on the  Design Methodology Management(DMM)  technology which provides a  framework for  the  system development.